Analysis of Bad Loan Management in Islamic Perspective in Village Owned Enterprises (Case Study in Pakis Putih Village, Kedungwuni District Pekalongan Regency) - Awali, Husni; Santi, Anisah (UMBanjarmasin, 2021)
Along with the development of Islamic Economics in the business world in Indonesia. BUMDes is a microfinance institution that has an important role that aims to improve the economic level of the community, as well as provide funds to the community to develop development in the form of providing credit. The purpose of this study was to determine the factors causing bad loans and how to manage them in an Islamic economic perspective in BUMDes Bina Pakis, Kedungwuni District, Pekalongan Regency. This type of research was conducted with a qualitative descriptive method. Researchers collect data by means of interviews through Social Media such as Whatsapp and Chat Messenger, as well as observations by thoroughly exploring the social situation to be studied. The results of the study can be said that (1) BUMDes